2020
DOI: 10.1021/acs.jafc.9b07860
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Bioavailability, Anti-inflammatory, and Anticancer Effects of Pterostilbene

Abstract: Supplementation with natural compounds found in fruits and vegetables has long been associated with a reduced risk of several types of cancer. Pterostilbene is a natural stilbenoid and a dimethylated analogue of resveratrol which is found primarily in blueberries. Pterostilbene exhibits a range of pharmacological properties, particularly anti-inflammatory and anticancer effects. Due to two methoxy groups in its skeleton, pterostilbene is more lipophilic than resveratrol and thus possesses higher intestinal per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 135 publications
2
67
0
Order By: Relevance
“…Our data cannot be compared to other studies since no data concerning the effects of pterostilbene on steatohepatitis have been reported so far. Nevertheless, the effects observed in the present study are in line with the anti-inflammatory action of pterostilbene observed in several diseases, including neuroinflammation, dermatitis, pancreatitis, inflammatory bowel disease, atherosclerosis and obesity [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our data cannot be compared to other studies since no data concerning the effects of pterostilbene on steatohepatitis have been reported so far. Nevertheless, the effects observed in the present study are in line with the anti-inflammatory action of pterostilbene observed in several diseases, including neuroinflammation, dermatitis, pancreatitis, inflammatory bowel disease, atherosclerosis and obesity [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
“…They share a common structure generally constituted by a C6‐C2‐C6 unit, i. e. a 1,2‐diphenylethylene moiety, with aromatic rings carrying one or more hydroxy groups. In the last decades, stilbenoids have been largely studied because of their diverse bioactivities, comprising cardioprotection, neuroprotection, anti‐diabetic and anti‐inflammatory properties, cancer prevention and treatment, [6] with trans ‐resveratrol and its methoxylated analogue trans ‐pterostilbene (Figure 1A, B) being the most deeply investigated compounds of this family [7–11] …”
Section: Introductionmentioning
confidence: 99%
“… 20 Its mechanism of action was that it induced cancer cell death by regulating the cell cycle, apoptosis, and autophagy, concomitantly inhibiting tumor angiogenesis, invasion, and metastasis. 21 However, the molecular biological mechanisms of PTS in hypoxia-induced HCC have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%